Histopathological effects of modern topical sealants on the liver surface after hepatectomy: an experimental swine study - Fonouni, Hamidreza; Khajeh, Elias; Ghamarnejad, Omid; Kashfi, Arash; Majlesara, Ali; Soleymanzadeh Gharabaghi, Negin; Konstantinidis, Lukas; Longerich, Thomas; Mehrabi, Arianeb; Kulu, Yakup (Scientific reports, 2019)
The present study aimed to determine the impact of different sealant materials on histopathological changes to the liver surface after liver resection. Thirty-six landrace pigs underwent left anatomical hemihepatectomy and were assigned to a histopathological control group (HPC, n = 9) with no bleeding control, a clinically simulated control group (CSC, n = 9) with no sealant but bipolar cauterization and oversewing of the liver surface, and two treatment groups (n = 9 each) with a collagen-based sealant (CBS) or a fibrinogen-based sealant (FBS) on resection surface. After postoperative day 6, tissue samples were histologically examined. There were no significant differences in preoperative parameters between the groups. Fibrin production was higher in sealant groups compared with the HPC and CSC groups (both p < 0.001). Hepatocellular regeneration in sealant groups was higher than in both control groups. A significantly higher regeneration was seen in the FBS group. Use of sealants increased the degree of fibrin exudation at the resection plane. Increased hepatocellular necrosis was seen in the CBS group compared with the FBS group. The posthepatectomy hepatocellular regeneration rate was higher in the FBS group compared with the CBS group. Randomized studies are needed to assess the impact of sealants on posthepatectomy liver regeneration in the clinical setting.
Gesehen am 01.08.2019